Study of the physical, chemical and biological processes in semi-intensive fishponds: development of a mathematical model as a tool for managing white seabream (Diplodus sargus) production - Serpa, Dalila do Rosário Encarnação (2015)
Semi-intensive aquaculture has been recognised as an “environmentally friendly” option. However, the low profitability and competitiveness of these systems compromise their economic viability. The optimization of production is thereby crucial for the sustainability of semiintensive pond aquaculture, and implies that fish yields are maximized with minimum impacts on the environment. Understanding the physical, chemical and biological processes occurring in fishponds is of outmost importance for defining farming strategies that optimize fish production. This knowledge is even more relevant when dealing with newly cultivated species, as the white seabream (Diplodus sargus). Due to the lack of information on the performance of this species in earth ponds, one of the main objectives of the present work was to study the physical, chemical and biological processes in white seabream ponds, over a production cycle. The most relevant results of this experimental work were that: i) the impacts of fish activity on bottom sediments are only noticeable above a fish biomass of 0.5 kg m-3 and a feeding rate of 5 kg d-1; ii) pond sediment and water quality was comparable to that of natural systems, suggesting that the assayed farming conditions ensure a good pond environment; and iii) pond water quality was strongly dependent on inflowing water and on benthic nutrient fluxes, emphasizing the relevance of optimum water exchange rates and sediment treatment to an efficient pond management. The other main objective of this work was to develop an ecological model to be used as a tool for managing semi-intensive systems, to improve their economic and environmental performance. The added value of a modeling approach is that, due to their ability to integrate the complexity of fishpond processes, models can be used to simulate the effect of different management scenarios on the pond environment and on the adjacent coastal systems. The model was implemented and tested with the white seabream as a case study, using data collected over the experimental work, together with literature data. Model construction was done in 3 steps: i) implementation of a biogeochemical model; ii) implementation of a fish Dynamic Energy Budget (DEB) model and iii) coupling of the two models. The biogeochemical model developed in this study is a mechanistic model that reproduces the dynamics of organic and inorganic nutrient (nitrogen and phosphorus) forms as well as of oxygen, in the pelagic and benthic compartments of an earth pond. This model not only helped understanding the interactions between pond variables and processes but also how pond structural features and operational parameters affect the water and sediment quality of pond systems. The fish DEB model was able to reproduce the growth of white seabream as well as of gilthead seabream (Sparus aurata), a traditionally cultivated species in semi-intensive ponds. This model was used to investigate which biological processes are more likely to influence fish performance and to explain inter-species growth variability. A comparison between the DEB model parameters of the two Sparidae revealed that white seabream lower growth rates are presumably linked to a higher energy demand for body maintenance and a lower feed absorption efficiency. The coupled model was able to reproduce fish pond dynamics, and was further used to simulate different management scenarios, related to stocking densities, water exchange rates and feeding strategies. Scenarios and standard farming conditions were compared in terms of their effects on pond water and sediment quality, as well as on final fish yields and nutrient discharges into the environment. Using the Analytical Hierarchical Process (AHP) methodology, scenarios were ranked in order to evaluate the best management options for optimizing white seabream production. Results revealed that doubling the standard stocking density and improving feed absorption efficiency, may enhance the performance of semi-intensive white seabream production systems. Aside from providing a tool for managing aquaculture systems, this work contains valuable information for defining guidelines on environmental standards (e.g. Maximum Recommended Values) for marine fish farming.